Electrochemical reduction of carbon dioxide to multicarbon (C) products: challenges and perspectives - Chang, Bin; Pang, Hong; Raziq, Fazal; Wang, Sibo; Huang, Kuo-Wei; Ye, Jinhua; Zhang, Huabin (Energy & environmental science, 2023)
Electrocatalytic CO 2 reduction has been developed as a promising and attractive strategy to achieve carbon neutrality for sustainable chemical production. Among various reduction products, multi-carbon (C 2+ ) compounds with higher energy density are desirable value-added products. Herein, we review and discuss the recent progress and challenges in preparing C 2+ products. We start with the elaboration of the most recent advancement of carbon-carbon coupling results and the newly proposed mechanisms, which are much more complicated than that of single-carbon products. The complex scenarios involved in the initial CO 2 activation process, the catalyst micro/nanostructure design, and mass transfer conditions optimization have been thoroughly discussed. In addition, we also propose the synergistic realization of high C 2+ product selectivity through the rational design of the catalyst and elaborate on the influence of electrolytes (anion/cation/pH/ionic liquid) using theoretical calculation analysis and machine learning prediction. Several in situ / operando techniques have been elaborated for tracking the structural evolution and recording the reaction intermediates during electrocatalysis. Additional insights into the triphasic interfacial reaction systems with improved C 2+ selectivity are also provided. By presenting these advances and future challenges with potential solutions related to the integral development of electrochemical reduction of carbon dioxide to C 2+ products, we hope to shed some light on the forthcoming research on electrochemical carbon dioxide recycling. This review analyzes advanced catalysts and C 2+ synthesis mechanisms based on theoretical explorations and in situ / operando characterizations. Triphasic interface optimization is discussed for the potential of industry-compatible stability.